Wind Energy Proceedings of the Euromech Colloquium - Peinke, Joachim; Schaumann, Peter; Barth, Stephan; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2007)
This book comprises reports on basic research, as well as research related to the practical exploitation and application of wind energy. "Wind Energy" comprehensively describes the atmospheric turbulent wind condition on different time scales, and the interaction of wind turbines with both wind and water flows, which are significant factors to consider for the design, operation and maintenance of wind turbines in offshore conditions. Topics of particular interest include: * wind climate & wind field * gusts, extreme events & turbulence * rotor aerodynamics & wake effects * power production & fluctuations * sea states & wave loads * materials (composites, steel, concrete) & fatigue * structural health monitoring.
Offshore Wind Power Meteorology -- Wave Loads on Wind-Power Plants in Deep and Shallow Water -- Time Domain Comparison of Simulated and Measured Wind Turbine Loads Using Constrained Wind Fields -- Mean Wind and Turbulence in the Atmospheric Boundary Layer Above the Surface Layer -- Wind Speed Profiles above the North Sea -- Fundamental Aspects of Fluid Flow over Complex Terrain for Wind Energy Applications -- Models for Computer Simulation of Wind Flow over Sparsely Forested Regions -- Power Performance via Nacelle Anemometry on Complex Terrain -- Pollutant Dispersion in Flow Around Bluff-Bodies Arrangement -- On the Atmospheric Flow Modelling over Complex Relief -- Comparison of Logarithmic Wind Profiles and Power Law Wind Profiles and their Applicability for Offshore Wind Profiles -- Turbulence Modelling and Numerical Flow Simulation of Turbulent Flows -- Gusts in Intermittent Wind Turbulence and the Dynamics of their Recurrent Times -- Report on the Research Project OWID – Offshore Wind Design Parameter -- Simulation of Turbulence, Gusts and Wakes for Load Calculations -- Short Time Prediction of Wind Speeds from Local Measurements -- Wind Extremes and Scales: Multifractal Insights and Empirical Evidence -- Boundary-Layer Influence on Extreme Events in Stratified Flows over Orography -- The Statistical Distribution of Turbulence Driven Velocity Extremes in the Atmospheric Boundary Layer – Cartwright/Longuest-Higgins Revised -- Superposition Model for Atmospheric Turbulence -- Extreme Events Under Low-Frequency Wind Speed Variability and Wind Energy Generation -- Stochastic Small-Scale Modelling of Turbulent Wind Time Series -- Quantitative Estimation of Drift and Diffusion Functions from Time Series Data -- Scaling Turbulent Atmospheric Stratification: A Turbulence/Wave Wind Model -- Wind Farm Power Fluctuations -- Network Perspective of Wind-Power Production -- Phenomenological Response Theory to Predict Power Output -- Turbulence Correction for Power Curves -- Online Modeling of Wind Farm Power for Performance Surveillance and Optimization -- Uncertainty of Wind Energy Estimation -- Characterisation of the Power Curve for Wind Turbines by Stochastic Modelling -- Handling Systems Driven by Different Noise Sources: Implications for Power Curve Estimations -- Experimental Researches of Characteristics of Windrotor Models with Vertical Axis of Rotation -- Methodical Failure Detection in Grid Connected Wind Parks -- Modelling of the Transition Locations on a 30% thick Airfoil with Surface Roughness -- Helicopter Aerodynamics with Emphasis Placed on Dynamic Stall -- Determination of Angle of Attack (AOA) for Rotating Blades -- Unsteady Characteristics of Flow Around an Airfoil at High Angles of Attack and Low Reynolds Numbers -- Aerodynamic Multi-Criteria Shape Optimization of VAWT Blade Profile by Viscous Approach -- Rotation and Turbulence Effects on a HAWT Blade Airfoil Aerodynamics -- 3D Numerical Simulation and Evaluation of the Air Flow Through Wind Turbine Rotors with Focus on the Hub Area -- Performance of the Risø-B1 Airfoil Family for Wind Turbines -- Aerodynamic Behaviour of a New Type of Slow-Running VAWT -- Numerical Simulation of Dynamic Stall using Spectral/hp Method -- Modeling of the Far Wake behind a Wind Turbine -- Stability of the Tip Vortices in the Far Wake behind a Wind Turbine -- Modelling Turbulence Intensities Inside Wind Farms -- Numerical Computations of Wind Turbine Wakes -- Modelling Wind Turbine Wakes with a Porosity Concept -- Prediction of Wind Turbine Noise Generation and Propagation based on an Acoustic Analogy -- Comparing WAsP and Fluent for Highly Complex Terrain Wind Prediction -- Fatigue Assessment of Truss Joints Based on Local Approaches -- Advances in Offshore Wind Technology -- Benefits of Fatigue Assessment with Local Concepts -- Extension of Life Time of Welded Fatigue Loaded Structures -- Damage Detection on Structures of Offshore Wind Turbines using Multiparameter Eigenvalues -- Influence of the Type and Size of Wind Turbines on Anti-Icing Thermal Power Requirements for Blades -- High-cycle Fatigue of “Ultra-High Performance Concrete” and “Grouted Joints” for Offshore Wind Energy Turbines -- A Modular Concept for Integrated Modeling of Offshore WEC Applied to Wave-Structure Coupling -- Solutions of Details Regarding Fatigue and the Use of High-Strength Steels for Towers of Offshore Wind Energy Converters -- On the Influence of Low-Level Jets on Energy Production and Loading of Wind Turbines -- Reliability of Wind Turbines.
Keywords: Renewable energy resources; Energy policy; Energy and state; Automotive engineering; Fluid mechanics; Vibration; Dynamical systems; Dynamics; Renewable and Green Energy; Energy Policy, Economics and Management; Automotive Engineering; Engineering Fluid Dynamics; Vibration, Dynamical Systems, Control; Renewable and Green Energy